The SIGHT questionnaire: A novel assessment tool for Satisfaction In Genital Hypospadias Treatment. Issue 1 (February 2017) - Ardelt, Peter U.; Cederqvist, Marco; Barth, Michael; Frankenschmidt, Alexander
Summary: Purpose: Psychosexual development is currently underrepresented in hypospadias outcome research. The aim of this study was to develop and validate a questionnaire addressing psychosexual long-term satisfaction, specifically of adolescent patients, after hypospadias repair. Materials and methods: In a multistep participative design we identified key interests of adolescent patients with hypospadias. Next, a questionnaire addressing specifically the psychosexual satisfaction of adolescents after hypospadias repair was established. A population of 109 former patients with hypospadias was then assessed using this questionnaire. Furthermore, functional and cosmetic aspects, behavioural anomalies, and sexual activity were investigated. Age-matched patients undergoing circumcision served as control patients. Possible influence factors on patient satisfaction were investigated. Clinical trial registry site: German Registry of Clinical Trials DRKS, Freiburg, Germany (Reference: DRKS00003432). Results: Key interests of adolescent patients were "normal appearance of the penis", "normal function of the penis regarding voiding and sexual activity", "no limitations regarding cosmetic appearance to others", "no limitations to sexual activity", and an "unimpaired masculine identity". The "Satisfaction In Genital Hypospadias Treatment" (SIGHT) questionnaire was developed using these items and using previously published evaluation systems. Nine questions address psychosexual aspects and two additional questions address current sexual activity. Internal consistency was high and retest reliability acceptable. The patient population showed a normal strength and difficulties score (SDQ). Overall satisfaction was high and similar to that of the control group. In a Spearman correlation a high SDQ value, erectile problems, and complications correlated negatively with satisfaction. Conclusion: To date, few studies have examined patients' satisfaction and psychosexuality. To our knowledge, the SIGHT questionnaire is the first to be developed participatively and in a stepwise fashion in collaboration with a paediatric psychologist and an open approach to determine items specifically important for adolescents. The SIGHT questionnaire can thus offer a relevant assessment of patients' psychosexual satisfaction. It is most suitable to supplement current strategies that so far mostly neglect the impact on psychosexual wellbeing.